Identifying Greener and Safer Plasticizers: A 4-Step Approach. (2nd August 2017) - Albert, Océane; Nardelli, Thomas C; Hales, Barbara F; Robaire, Bernard
Abstract: The health and economic burden of endocrine disrupting chemicals, such as the plasticizer di(2-ethylhexyl) phthalate (DEHP), is prompting industry to develop alternatives. However, the absence of requirements for manufacturers to ensure the safety of these alternatives has led to the generation of replacements that may have similar or worse effects than the original chemicals. Consequently, there is increasing recognition by scientists, regulators and industry that proactive approaches are needed to develop safe chemical substitutes. We propose a 4-step approach for the design, characterization and toxicological testing of responsible alternative chemicals that we illustrate with our ongoing studies on DEHP replacements. Our approach is comprised of: (1) the design and characterization of alternative chemicals based on innovative chemical structures and environmental considerations; (2) large-scale in vitro cell-based high throughput and selective ex vivo studies to preselect the most innocuous alternatives; (3) an acute toxicity in vivo study to rule out overt toxicity of the selected candidates; and (4) an in utero and lactational exposure study comparing the effects of selected candidates to those currently in use, emphasizing commonly described phenotypes after exposure to the latter. Using this 4-step approach, we have identified 2 alternative chemicals displaying good plasticizing properties, better biodegradability, and less leaching than DEHP without any apparent toxicity in vivo . This process has thus far proven useful in the proactive identification of responsible chemical replacements for DEHP.